Endogenous Knowledge of the Attie People on Antischistosomiasis Medicinal Plants in the Adzope Health District, CÃ´te d’Ivoire - Bene, Kouadio; Ouedje, Eppoue Romuald; Koffi, AkessÃ© Georges; Tra Bi, Boli Francis; Sylla, Youssouf; Fah , Monh Alice; Moyabi, Any Georges Armel; Koukakou, Donthy Kouakoubah Richard; Kone, Mamidou Witabouna (European Scientific Journal, ESJ, 2022)
Schistosomiasis or bilharziasis is a parasitic disease caused by flatworms or plathelminthes: bilharzias or schistosomes that live in the venous vascular system. This disease is a major public health problem in countries located in the tropics and subtropics. The general objective of this work was to contribute to the eradication of schistosomiasis in CÃ´te d’Ivoire by highlighting the endogenous knowledge of the Attie people on the medicinal plants used for the treatment of schistosomiasis in the Health District of Adzope. An ethnobotanical survey was conducted among practitioners of traditional medicine (TMP), using a semi-structured interview associated with the show-and-tell technique. A total of 33 medicinal species have been listed. They are divided into 31 genus and 21 botanical families with a predominance of Annonaceae, Asteraceae, Euphorbiaceae and Fabaceae, each with three species. The most cited species are Combretum paniculatum (CF = 14.79%) and Mareya micrantha (CF = 10.56%). The leaves are the most used organs; the decoction is the main mode of preparation of the recipes which are generally administered orally. The results of this study constitute a valuable database for further research in pharmacology and phytochemistry.